2005
DOI: 10.1359/jbmr.050509
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Effects of Raloxifene After 8 Years: Results from the Continuing Outcomes Relevant to Evista (CORE) Study

Abstract: In the CORE breast cancer trial of 4011 women continuing from MORE, the incidence of nonvertebral fractures at 8 years was similar between placebo and raloxifene 60 mg/day. CORE had limitations for assessing fracture risk. In a subset of 386 women, 7 years of raloxifene treatment significantly increased lumbar spine and femoral neck BMD compared from the baseline of MORE. Introduction:The multicenter, double-blind Continuing Outcomes Relevant to Evista (CORE) trial assessed the effects of raloxifene on breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0
21

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(136 citation statements)
references
References 33 publications
5
110
0
21
Order By: Relevance
“…Therefore, we do not think that our findings of no increase of BMD at the non-vertebral sites rule out the potential effects of RLX to reduce the risk of non-vertebral fractures. Actually, its effects on prevention of hip fractures in those patients, mostly Caucasian, with high risk of fractures, have already been demonstrated in MORE study [20], although not in all of the patients. A large-scale double-blinded prospective randomized study to evaluate its effects on prevention of fractures, vertebral or non-vertebral, is warranted for Japanese postmenopausal women.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, we do not think that our findings of no increase of BMD at the non-vertebral sites rule out the potential effects of RLX to reduce the risk of non-vertebral fractures. Actually, its effects on prevention of hip fractures in those patients, mostly Caucasian, with high risk of fractures, have already been demonstrated in MORE study [20], although not in all of the patients. A large-scale double-blinded prospective randomized study to evaluate its effects on prevention of fractures, vertebral or non-vertebral, is warranted for Japanese postmenopausal women.…”
Section: Discussionmentioning
confidence: 94%
“…(36) Only raloxifene and bazedoxifene have long-term data, and treatment discontinuation has only been studied in raloxifene. (37)(38)(39) The magnitude of the effect of raloxifene on BMD and BTMs is generally lower than that of standard-dose HT, (40) and fracture protection appears confined to the spine. (41) The Continuing Outcomes Relevant to Evista (CORE) study indicated that 7 years of raloxifene therapy maintained the initial increments seen in spine and hip BMD over 3 years, but showed no further gains (Table 1).…”
Section: Selective Estrogen Receptor Modulatorsmentioning
confidence: 99%
“…(41) The Continuing Outcomes Relevant to Evista (CORE) study indicated that 7 years of raloxifene therapy maintained the initial increments seen in spine and hip BMD over 3 years, but showed no further gains (Table 1). (38) Long-term BTM data (!5 years) were not available. No effect on nonvertebral fracture incidence was seen in the MORE, (42) CORE, (38) or the Raloxifene Use for the Heart (RUTH) trial of over 10,000 women with documented or at high risk for coronary heart disease.…”
Section: Selective Estrogen Receptor Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raloxifene therapy suppresses the bone turnover to normal premenopausal range, thereby increasing bone mineral density (BMD) in the spine, hip and total body [3,4], reducing the risk for vertebral fractures [5] but not changing non-vertebral fracture risk [6]. After peroral application, raloxifene undergoes a rapid absorption, an extensive first-pass metabolism and an entero-hepatic cycling.…”
Section: Introductionmentioning
confidence: 99%